The geographical clustering of Chinese media production - Keane, Michael (Routledge (Taylor & Francis Group), 2015)
Studies of China’s media have in the main privileged the nation-state. As the home of China Central Television (CCTV), the People’s Daily and a host of national regulatory bureaus, Beijing has long symbolised the hegemony of the Chinese Communist Party (CCP). At least this was the case until the late 1990s when provincial media began to exert their influence. Many media operations took their commercial opportunities when broadcasters were granted access to extend their signals nationally through designated satellite channels. By the end of the first decade of the 2000s some of these broadcasters achieved extensive geographical coverage by entering into mergers and alliances with internet businesses such as Sohu and Tudou.